The complete guide to patios : plan, build and maintain - Schmidt, Philip (Creative Pub. International, 2007)
"A comprehensive guide that includes an introduction to the most popular building materials: a fool-proof method for design, planning and layout; detailed step-by-step projects to help readers build any one of 12 different types of patios; instructions for building popular patio accessories and features; and tips for maintaining and repairing all types of patios"--Provided by publisher.